Features of Apoptosis, Induced by Temperature Reduction - Shchenyavsky, I.I.; Gulevsky, A.K.; Akhatova, Yu.S. (Problems of Cryobiology and Cryomedicine, 2017)
We summarised and analysed here the findings on apoptosis contribution into the cell damages, caused by temperature deviation from the physiological norm (below 37°C). The participation of the caspases, causing the disintegration of anti-apoptotic Bcl2 family proteins and proteolysis of the DNAase inhibitor, responsible for DNA fragmentation in the apoptosis, induced by a moderate cell cooling, was shown. An important role in cold adaptation mechanism belongs to the RNA-binding protein (cold-inducible RNAbinding protein, CIRP), which is capable to prevent the oxidative stress-induced apoptosis development. We reported here the data, confirming the participation of reactive oxygen species and antioxidant cell components: superoxide dismutase and human peroxiredoxin 1 in apoptosis and cold adaptation.
Особенности апоптоза, индуцированного снижением температуры
Особенности апоптоза, индуцированного снижением температуры
Keywords: apoptosis, hypothermia, cell cultures, apoptosis induction, caspases, oxidative stress, antioxidant system.